WERYFIKACJA OSIĄGNIĘCIA PRZEDMIOTOWYCH EFEKTÓW KSZTAŁCENIA/UCZENIA SIĘ W RAMACH PRAKTYKI NAUCZYCIELSKIEJ – WYBRANE MODELE - Anna Bąk-Średnicka (Neofilolog, 2019)
Quality assessment of intended learning outcomes in teaching practice should reflect current directions in educating preservice teacher candidates. Moreover, it should correspond with recent studies on human behavior in social psychology. A trainee teacher applies the knowledge acquired at university only when confronted by all manner of problems in the complex pedagogical reality. Therefore, the intended learning outcome, which is a key factor in quality teacher education and which should undergo quality assessment (Journal of Laws, 2012), is pedagogical acuity. Pedagogical acuity, so-called “sensitivity to problems” (Kwiatkowska, 1988: 103, 105), is the ability on the part of trainee teachers to reflect-inaction and to reflect-on-action by identifying classroom and out-of-classroom problems and dealing with them in a creative way. The development of pedagogical acuity is not an automatic process and it depends on trainees’ readiness to take autonomous decisions. The aim of the article is twofold. Firstly, it compares three models of assessment, which apply alternative evaluation methods of intended learning outcomes in teaching practice, with regard to the development of autonomous behavior on the part of the trainee. They offer forms of alternative assessment in which narrative texts play a central role; these include discussions, dialogues, journals and/or diaries. Secondly, the article analyses teacher education programs at Polish universities, considering those available online, from the perspective of developing autonomous behavior during teaching practice. The findings reveal that roughly one third of teacher education programs apply alternative assessment in teaching practice. In concluding remarks the author reflects on the significant gap between the assessment preferences of academicians, and proven models applying alternative evaluation methods available in literature mainly in the form of one-off projects.